2014
DOI: 10.1002/iroh.201301678
|View full text |Cite
|
Sign up to set email alerts
|

Habitat type as strongest predictor of the body size distribution of Chydorus sphaericus (O. F. Müller) in small water bodies

Abstract: Chydorus sphaericus, a cladoceran characterized by a wide range of distribution, is often numerous in various water habitats. Its body size is a consequence of environmental characteristics and physiology. The aim of the study focused on the distribution of body size and densities of C. sphaericus in relation to environmental conditions represented by: (i) habitat types (elodeids, helophytes, and the open water); (ii) specific pond types (forest and field); (iii) pond size (surface area); (iv) the presence/lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…The importance of structurally complex habitat as a refuge from predators especially confirmed research on water organisms. For example, the study of Chydorus sphaericus species belonging to Crustacea revealed that larger specimens occurred among macrophytes, and the smallest ones were in the open water zone, which indicated that vegetation was a significant refuge against predators [65].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of structurally complex habitat as a refuge from predators especially confirmed research on water organisms. For example, the study of Chydorus sphaericus species belonging to Crustacea revealed that larger specimens occurred among macrophytes, and the smallest ones were in the open water zone, which indicated that vegetation was a significant refuge against predators [65].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, widened channels are expected to have larger areas with direct sunlight (due to reduced shading from riparian trees) and low water depth, which probably positively affected hydrophyte growth as also noted by Makkay et al (2008). Due to the importance of elodeid species as habitats and refuges for macroinvertebrates and fish (Strayer & Malcom, 2007;Basińska et al, 2014), the positive effect of widening on elodeids could potentially also have cascading ecological effects. Instream measures in our study comprised, among others, bolder replacement and gravel additions to increase salmonid spawning areas.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the partial loss of aquatic macrophytes (Steffen et al, 2013) not only has severe consequences for macrophyte diversity but might also have cascading ecological effects due to the macrophytes' importance as habitat for other organism groups (Heck Jr. & Crowder, 1991;Strayer & Malcom, 2007;Basińska et al, 2014). Furthermore, aquatic macrophytes also function as ecosystem engineers (Asaeda et al, 2010;O'Hare et al, 2011) and influence river processes such as metabolism and nutrient cycling (Tabacchi et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Chydorus sphaericus is one the most common benthic cladoceran species (Giere, ), and has been reported living in the littoral zones of lakes among macrophyte vegetation and on benthic substrates that are rich in organic material (e.g. Giere, ; Basińska et al ., ), as well as in the water column in the open water zone of eutrophic lakes and ponds (Vijverberg & Boersma, ). Therefore, this taxa is probably better adapted to detrital food sources compared to large‐bodied pelagic cladocerans (Vijverberg & Boersma, ).…”
Section: Methodsmentioning
confidence: 99%
“…This is misleading since many cladocerans such as Chydorus sphaericus (Chydoridae) and cyclopoid copepods have been reported as living among macrophytes, organic rich benthos, and water column of lentic ecosystems (e.g. Giere, ; Basińska et al ., ). They perform diel vertical migrations concentrating near the bottom during the day and on the surface at night (Lauridsen et al ., ; Casper & Thorp, ; Semyalo, Nattabi & Larsson, ; Wallace et al ., ).…”
Section: Introductionmentioning
confidence: 97%